Investigating Factors in Quality of Work-life in Indian Garment Industry at Bangalore - Kishore SV, Krishna; Banerjee, Jayanta; Kiran, Prabha; Moorthy, Vasudevan (Thailand and The World Economy, 2022)
The Indian manufacturing sector has a long way to go in enhancing work-life standards for employees. Low standards of work-life hamper the productivity of an organization. Most employees of garment manufacturing units in Bengaluru are from outer rural areas. They come in search of employment in garment units. Though there are labour acts and labour laws, most of the manufacturing units provide poor job environments for employees. This leads to fluctuations in the performance of employees and would have detrimental effects on their health and performance, resulting in attrition. Quality of work life is the solution. This paper aims at unravelling factors leading to recognition of work-life standards so those garment units can work in that dimension to solve their productivity issues and also improve the happiness of their employees. A descriptive approach was made to attain objectives with survey-based data collection. The collected data were subjected to exploratory factor analysis and multiple regression analysis. The study found welfare and safety lead to a quality of work-life in garment units. More cross-sectoral studies are suggested to understand the blend of factors defining the quality of work life and arrive at a generalized model nation-wide. This generalization in the long term should be a key decision-making point for safety and welfare policy development in the world.